Curcumin reduces inflammation in rat apical periodontitis - Justo, Mariana Pagliusi [UNESP]; Cardoso, Carolina de Barros Morais [UNESP]; Cantiga-Silva, Cristiane [UNESP]; Oliveira, Pedro Henrique Chaves de [UNESP]; Araújo, Gustavo Sivieri de [UNESP]; Azuma, Mariane Maffei [UNESP]; Ervolino, Edilson [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Wiley-Blackwell, 2022)
Aim The aim of the study was to evaluate the effect of systemic curcumin administration on the severity of apical periodontitis (AP). Methodology Forty male Wistar rats weighing 250-280 g each, age 2.5 months, were distributed into four groups (n = 10): control untreated rats (C), control rats treated with curcumin (CUR), rats with pulp exposure-induced apical periodontitis (AP) and rats with pulp exposure-induced apical periodontitis treated with curcumin (AP-CUR). Curcumin treatment was administered orally once daily for 15 days before pulp exposure and continued for 30 days after pulp exposure. The rats were sacrificed at 30 days, and the jaws were collected and reconstructed in a programme specific for micro-CT. The jaws were processed for analysis of the inflammatory process using haematoxylin and eosin staining and immunohistochemical assays for interleukin tumour necrosis factor alpha (TNF-alpha), interleukin (Il)-6 and Il-1 beta. Tartrate-resistant acid phosphatase (TRAP) and osteocalcin (OCN) staining were used to analyse the resorptive process on the bone surface of periapical area. Kruskal-Wallis with Dunn's test was performed for nonparametric data and anova with Tukey's test for parametric data, p < .05. Results Micro-CT revealed no statistically significant differences in bone resorption between the AP and AP-CUR groups (p > .05). The levels of inflammatory cell infiltration and immunoreactivity for the proinflammatory cytokines TNF-alpha, Il-6 and Il-1 beta were significantly higher in the periapical lesions of the AP group than in the AP-CUR group (p < .05). The number of TRAP-positive multinucleated cells was higher in the AP group than in the AP-CUR group (p < .05). In OCN-positive cells, no differences were observed between the AP and AP-CUR groups (p > .05). Conclusions Oral supplementation with curcumin had a significant effect on the AP severity in rats, suggesting an anti-inflammatory effect of curcumin on AP development.
Keywords: Apical periodontitis; Curcumin; Cytokine; Endodontic infection